2009
DOI: 10.1128/jb.01556-08
|View full text |Cite
|
Sign up to set email alerts
|

Seawater-Regulated Genes for Two-Component Systems and Outer Membrane Proteins in Myxococcus

Abstract: When salt-tolerant Myxococcus cells are moved to a seawater environment, they change their growth, morphology, and developmental behavior. Outer membrane proteins and signal transduction pathways may play important roles in this shift. Chip hybridization targeting the genes predicted to encode 226 twocomponent signal transduction pathways and 74 outer membrane proteins of M. xanthus DK1622 revealed that the expression of 55 corresponding genes in the salt-tolerant strain M. fulvus HW-1 was significantly modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…Salt-tolerant Myxococcus fulvus strain HW-1 exhibits remarkable changes in the social behavior when cultured in media of different saltwater concentrations. Our previous studies have indicated that maintenance and reinforcement of social behavior are important for HW-1 to adapt to oceanic conditions Zhang et al, 2007;Pan et al, 2009). In this study, the phenotype of the mutant strain YLH0401 indicated that the insertional inactivation of a single horizontally transferred gene led to dramatic phenotypic changes, including dispersed growth, defective fruiting body formation and sporulation, decreased ECM production and S-motility, and seawater intolerance.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Salt-tolerant Myxococcus fulvus strain HW-1 exhibits remarkable changes in the social behavior when cultured in media of different saltwater concentrations. Our previous studies have indicated that maintenance and reinforcement of social behavior are important for HW-1 to adapt to oceanic conditions Zhang et al, 2007;Pan et al, 2009). In this study, the phenotype of the mutant strain YLH0401 indicated that the insertional inactivation of a single horizontally transferred gene led to dramatic phenotypic changes, including dispersed growth, defective fruiting body formation and sporulation, decreased ECM production and S-motility, and seawater intolerance.…”
Section: Discussionmentioning
confidence: 64%
“…For example, mutation of the S-motility-related gene locus mts (homolog of which in the model strain M. xanthus DK1622 is located at MXAN_1333-1337) led to a simultaneous decrease in salt tolerance . Two seawaterregulated genes-the two component system gene Tc105 (MXAN_4042 in DK1622) and outermembrane protein gene Om031 (MXAN_3016 in DK1622)-are both involved in social behavior and salt tolerance (Pan et al, 2009). In this study, we report an association between the salt-tolerance adaptation and social behavior in a new mutant of M. fulvus HW-1.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…On the basis of recent studies, it has been suggested that the Nla6S/Nla6 TCS may be a general regulator of stress-associated genes (59,66). Presumably, the confirmed developmental targets of the Nla6S/Nla6 TCS fall into this category, since they show Nla6-dependent activation 1 h after M. xanthus cells encounter starvation-induced stress (59).…”
Section: Figmentioning
confidence: 99%